Modelling a D-shaped Sensor for Transformer Oil Refractive Index Detection - Md Yasin, Muhammad Zakir; Ngajikin, Nor Hafizah; Aminah Ali, Siti Hajar; Abdul Kadar, Muhammad Sazlan; Che Abd Rashid, Nurfatihah; Talib, Mohd Aizam; Cholan, Noran Azizan (semarak ilmu, 2024)
A simulative-based investigation using COMSOL Multiphysics software has been carried out to study the sensing performance of a D-shaped refractive index (RI) sensor in the ageing detection of transformer oil. In this work, a D-shaped plastic optical fiber (POF) RI sensor has been modelled to have a curve surface for its D region. This surface that exposed some parts of the POF core and cladding, enables interaction between the transformer oil located in the D region with optical light propagate in the POF. The simulation has been conducted to study the effect of D region diameter towards the sensor electric field distribution, sensitivity and linearity performances. The transformer oil RI value is ranging from 1.4785 to 1.4807, which is based on the transformer oil samples provided by the TNB Labs Sdn Bhd. The RI variations affect the evanescent wave's penetration depth, thus varying the electric field distribution in the sensor. In this investigation, the 0.75cm diameter of the D-shaped POF RI sensor exhibits the highest sensitivity of -0.1426 RIU-1 with a linearity of 0.9998 at 660nm wavelength. The proposed D-shaped RI sensor offers a sensor with high linearity performance sensor to be applied in transformer oil ageing detection.